2016
DOI: 10.1111/mec.13771
|View full text |Cite
|
Sign up to set email alerts
|

Differential gene expression according to race and host plant in the pea aphid

Abstract: Host-race formation in phytophagous insects is thought to provide the opportunity for local adaptation and subsequent ecological speciation. Studying gene expression differences amongst host races may help to identify phenotypes under (or resulting from) divergent selection and their genetic, molecular and physiological bases. The pea aphid (Acyrthosiphon pisum) comprises host races specializing on numerous plants in the Fabaceae and provides a unique system for examining the early stages of diversification al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 120 publications
4
56
1
Order By: Relevance
“…Consequently, there is no effector category in standard gene ontologies, and researchers would not detect enriched differential expression of effectors across hosts using standard enrichment analyses. Furthermore, with one exception [20], the published RNAseq-based differential expression analyses of insect diet variation have studied species with transient connections with their host plants (at least in comparison to sap-sucking insects), and might not be expected to strongly manipulate their host’s induced defenses.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, there is no effector category in standard gene ontologies, and researchers would not detect enriched differential expression of effectors across hosts using standard enrichment analyses. Furthermore, with one exception [20], the published RNAseq-based differential expression analyses of insect diet variation have studied species with transient connections with their host plants (at least in comparison to sap-sucking insects), and might not be expected to strongly manipulate their host’s induced defenses.…”
Section: Introductionmentioning
confidence: 99%
“…) and gene expression (Eyres et al . ) has all found indications that chemosensory genes differ between pea aphid races. Although these studies confirm the value of further investigation of chemosensory genes in pea aphids and provide us with a set of potentially interesting target chemosensory genes, this type of broad genomic study is prone to problems of false positives, as well as questionable reliability and repeatability (François et al .…”
Section: Introductionmentioning
confidence: 99%
“…Comparative gene expression studies enable the identification of biological functions involved in the adaptation of organisms to their surrounding environments 15 . By proteomics approach, Celorio-Mancera et al demonstrated the expression of CSP1 changed in response to the caterpillar diet in the mandibular glands.…”
Section: Discussionmentioning
confidence: 99%
“…One intriguing possibility is that, in midgut, CSPs also could perceive signal chemicals from food resources, thus to mediate feeding behaviors. The analysis of gene expression in response to different treatments have potential to understand the biological function of such genes in adapting surrounding environments 15 and the binding of an external ligand to the CSPs could result in action potentials and contribute to subsequent behaviors 16 . Eventually, studying of CSPs expression variations in response to different plant resources and binding affinities may elucidate the role of CSPs in midgut.…”
Section: Introductionmentioning
confidence: 99%